From the Ottomans to the Republicans: Accommodation of the Kemalist content in between the spiritual and the temporal - (:unkn) unknown (My University, 2013)
Kemalist içeriktekidünyevilik, özellikle, tek parti süresinde uygulanan kemalist laiklik ilkesine olan alakası söz konusu olduğunda, pozitivist ideolojiyle bağlantılıdır.Sonuç olarak Osmanlı “teokratik” yapısı özel bir durum içerse de, Osmanlı devletine karşıt niteliğiyle Kemalist içerik kamu alanında maneviyatın ifadesine de karşıt olmuştur. Diğer yandan, liberal İslam’ın kamu alanınatekrar dâhil olması, bizzat kemalizmin uğradığı değişimle ilgilidir. Bu makale, dolayısıyla, kemalizmin bir süreç olarak, farklı tarihsel çerçeveler gereğince dönüşebilir niteliğini savunmaktadır. Bunun karşılığında dünyevi ve manevi arasında kemalizmin uzlaşımı, kemalizmin yeniden yorumuna dayanmıştır. Bu ise, bir yandan Türkiye’ye uluslararası sahada yeni bir rol model yüklerken, diğer yandan Osmanlı İmparatorluğu’ndan bu yana süregelen dinin devlete bağlı statüsüne de dayanmıştır. Sonuç olarak makale, kemalizmin maneviyatla olan uzlaşımının, açık uçlu bir süreç olarak,kemalizmin yeniden yoruma izin verebilmesiyle gerçekleştiğini savunmaktadır.

The temporal in the kemalist content, resulted from the positi- vist ideology, especially as it relatedto the kemalist principle of secularism during the single party period. Consequently, even though the Ottoman “theocracy” had been a special case, the kemalist content in its opposition to the Ottoman State, op- posed as well the spiritual element in public sphere. The rein- tegration of liberal Islam in public corresponded on the other hand,tokemalismbeing transformed. The article proposes that the kemalism as a process could transform in relationship to different historical contexts. In turn, the accommodation of the kemalist content in between the temporal and the spiri- tual depended on kemalism’s getting reinterpreted. This,while attributed a new role model to Turkey on the international scene, obeyed nevertheless the status of religion since the Ottoman Empireas submitted to State. The article concludes that kemalist accommodation to the spiritual has only been possiblewithin the reinterpretation of kemalism because the kemalist ideology, as an open ended process, permitted it.
Osmanlılardan Cumhuriyetçilere: Manevi ve dünyevi arasında Kemalist içeriğin uzlaşımı
Keywords: İktisat; İşletme